La estética como experiencia sensorial y cognitiva - Orellana Chavez, Douglas Enrique (Machala, 2024)
Aesthetics is the study of the perception and judgment of the beautiful and the unpleasant in art and nature. Aesthetics is a sensory and cognitive experience, as it involves both the senses and thought. Aesthetics allows us to appreciate the variety and richness of shapes, colors, sounds, smells, tastes, and textures around us, and it also makes us question the meaning, value, and purpose of what we see, hear, touch, smell, and taste.Beauty is one of the central concepts of aesthetics. Beauty refers to the quality of something that produces pleasure or admiration when perceived by the senses or mind. Beauty is subjective, as it depends on each person's tastes, preferences, and values. What is beautiful for one may not be beautiful for another. Beauty is also relative, as it varies depending on context, culture, and era. What is beautiful in one place or time may not be beautiful in another. Beauty is an ideal that is sought and created, but it is also questioned and criticized. Unpleasantness is the opposite of beautiful. Unpleasantness refers to the quality of something that produces rejection or aversion when perceived by the senses or mind. What is unpleasant is also subjective and relative, as it depends on the criteria and circumstances of each person. What is unpleasant for one may not be unpleasant for another. What is unpleasant in one place or time may not be unpleasant in another. The unpleasant is a challenge that is avoided or faced, but it is also explored and transformed. Aesthetics is a discipline that helps us understand and appreciate the diversity and complexity of artistic and natural manifestations. Aesthetics invites us to reflect on our own judgments and sensations, and to dialogue with those of others. Aesthetics enriches us as human beings, as it allows us to experience the pleasure and challenge of the beautiful and the unpleasant. Within art, one of the oldest and most universal forms of aesthetic expression is sculpture. Sculpture is an art form that involves creating three-dimensional works by modeling, carving, assembling, or casting various materials. Sculpture can depict human figures, animals, objects, abstract or symbolic shapes. Sculpture can have religious, commemorative, decorative, or expressive purposes.Sculpture involves physical and manual labor, which requires skill, precision, and creativity. The sculptor must choose the right material for his work, taking into account its properties, its resistance, its texture and its color. The sculptor must also master the techniques and tools necessary to manipulate the material, whether to shape it, to join it or to separate it. The sculptor must also take into account the space, light, and perspective surrounding his work, and how these elements influence its appearance and meaning.Plaster casting is a technique for reproducing sculptures that consists of making a mold of the original work and then filling it with liquid plaster, which when hardened takes the shape of the model. Plaster casting makes it possible to obtain exact and detailed copies of the sculptures, which can be used for educational, conservation or dissemination purposes. Plaster casting has been fundamental to the knowledge of the history of art, since thanks to it has been possible to preserve and study works from classical antiquity and other periods. Plaster is an inexpensive material, easy to obtain and handle, which offers great fidelity to the original. Plaster is also a versatile material, which can be painted, gilded, sculpted or combined with other materials. Gypsum has, however, some disadvantages, such as its fragility, its weight, and its sensitivity to moisture and biological agents. Plaster therefore requires special care for its conservation and restoration. Sculpture and plaster casting are two aspects of aesthetics that show us the human capacity to create and reproduce forms, to imitate and innovate, to admire and to learn. Sculpture and plaster casting are two ways of expressing and communicating ideas, emotions and values, of capturing and transmitting beauty and displeasure, of facing and overcoming aesthetic challenges.
La estética es el estudio de la percepción y el juicio de lo bello y lo desagradable en el arte y la naturaleza. La estética es una experiencia sensorial y cognitiva, ya que involucra tanto los sentidos como el pensamiento. La estética nos permite apreciar la variedad y la riqueza de las formas, los colores, los Sonidos, los olores, los sabores y las texturas que nos rodean, y también nos hace cuestionarnos sobre el significado, el valor y el propósito de lo que vemos, oímos, tocamos, olemos y gustamos. La belleza es uno de los conceptos centrales de la estética. La belleza se refiere a la cualidad de algo que produce placer o admiración al ser percibido por los sentidos o la mente. La belleza es subjetiva, ya que depende de los gustos, las preferencias y los valores de cada persona. Lo que es bello para uno puede no serlo para otro. La belleza también es relativa, ya que varía según el contexto, la cultura y la época. Lo que es bello en un lugar o momento puede no serlo en otro. La belleza es un ideal que se busca y se crea, pero también se cuestiona y se critica.Lo desagradable es lo opuesto a lo bello. Lo desagradable se refiere a la cualidad de algo que produce rechazo o aversión al ser percibido por los sentidos o la mente. Lo desagradable también es subjetivo y relativo, ya que depende de los criterios y las circunstancias de cada persona. Lo que es desagradable para uno puede no serlo para otro. Lo que es desagradable en un lugar o momento puede no serlo en otro. Lo desagradable es un reto que se evita o se enfrenta, pero también se explora y se transforma.La estética es una disciplina que nos ayuda a comprender y apreciar la diversidad y la complejidad de las manifestaciones artísticas y naturales. La estética nos invita a reflexionar sobre nuestros propios juicios y sensaciones, y a dialogar con los de los demás. La estética nos enriquece como seres humanos, ya que nos permite experimentar el placer y el desafío de lo bello y lo desagradable. Dentro del arte, una de las formas más antiguas y universales de expresión estética es la escultura. La escultura es una forma de arte que consiste en crear obras tridimensionales mediante el modelado, el tallado, el ensamblaje o el vaciado de diversos materiales. La escultura puede representar figuras humanas, animales, objetos, formas abstractas o simbólicas. La escultura puede tener fines religiosos, conmemorativos, decorativos o expresivos. La escultura implica un trabajo físico y manual, que requiere de habilidad, precisión y creatividad. El escultor debe elegir el material adecuado para su obra, teniendo en cuenta sus propiedades, su resistencia, su textura y su color. El escultor debe también dominar las técnicas y las herramientas necesarias para manipular el material, ya sea para darle forma, para unirlo o para separarlo. El escultor debe también tener en cuenta el espacio, la luz y la perspectiva que rodean a su obra, y cómo estos elementos influyen en su apariencia y su significado. El vaciado en yeso es una técnica de reproducción de esculturas que consiste en hacer un molde de la obra original y luego rellenarlo con yeso líquido, que al endurecerse toma la forma del modelo. El vaciado en yeso permite obtener copias exactas y detalladas de las esculturas, que se pueden usar para fines didácticos, de conservación o de difusión. El vaciado en yeso ha sido fundamental para el conocimiento de la historia del arte, ya que gracias a él se han podido preservar y estudiar las obras de la antigüedad clásica y de otras épocas. El yeso es un material barato, fácil de conseguir y de manejar, que ofrece una gran fidelidad al original. El yeso también es un material versátil, que se puede pintar, dorar, esculpir o combinar con otros materiales. El yeso tiene, sin embargo, algunas desventajas, como su fragilidad, su peso y su sensibilidad a la humedad y a los agentes biológicos. El yeso requiere, por tanto, de un cuidado especial para su conservación y restauración. La escultura y el vaciado en yeso son dos aspectos de la estética que nos muestran la capacidad humana de crear y de reproducir formas, de imitar y de innovar, de admirar y de aprender. La escultura y el vaciado en yeso son dos formas de expresar y de comunicar ideas, emociones y valores, de plasmar y de transmitir la belleza y el desagrado, de enfrentar y de superar los retos estéticos.
Keywords: ARTE; ESTETICA; ESCULTURA; PSICOLOGIA; HISTORIA DEL ARTE; BELLEZA; GROTESCO; SOCIAL; SOCIEDAD; EXPERIENCIA